Bacillus subtilis DNA Polymerase III Is Required for the Replication of the Virulent Bacteriophage φe - Lavi, Uri (1974)
The virulent phage φe of Bacillus subtilis which contains hydroxymethyluracil in its DNA requires host DNA polymerase III for its DNA replication. DNA polymerase III(ts) mutant cells infected with φe at restrictive temperatures do not support phage DNA synthesis. However, φe grows normally both at low and high temperatures in the mutant's parent strain and in spontaneous DNA polymerase III(+) revertants isolated from the mutant strain. Temperature-shift-down experiments with φe-infected cells having thermosensitive DNA polymerase III (pol III(ts)) indicate that at 48 C the thermolabile DNA polymerase III is irreversibly inactivated and has to be synthesized de novo after the shift to 37 C, before phage DNA synthesis can begin. Temperature-shift-up experiments with φe-infected mutant cells show that phage replication is arrested immediately after the temperature shift and indicate that φe requires DNA polymerase III throughout its replication stage.